POLITICIZATION AND SOCIAL TRANSFORMATIONS IN THE RURAL VILLAGES OF THE STATE OF BUENOS AIRES,1852-1861 - Zubizarreta, Ignacio (2018)
The purpose of this article is to analyze the process of legitimization of the political elites of Buenos Aires in the intricate rural sphere as a result of a process promoted by several neighboring rural sectors. Its aim is to contribute to a better understanding of the post-Caseros social and political transformations that began in the heat of a greater press freedom and of the rise of recreational and political clubs.